Lung-Protective Ventilation Attenuates Mechanical Injury While Hypercapnia Attenuates Biological Injury in a Rat Model of Ventilator-Associated Lung Injury - Ismaiel, Nada; Whynot, Sara; Geldenhuys, Laurette; Xu, Zhaolin; Slutsky, Arthur S.; Chappe, Valerie; Henzler, Dietrich (Frontiers in Physiology, 2022)
Background and Objective: Lung-protective mechanical ventilation is known to attenuate ventilator-associated lung injury (VALI), but often at the expense of hypoventilation and hypercapnia. It remains unclear whether the main mechanism by which VALI is attenuated is a product of limiting mechanical forces to the lung during ventilation, or a direct biological effect of hypercapnia. Methods: Acute lung injury (ALI) was induced in 60 anesthetized rats by the instillation of 1.25M HCl. Ten rats each were randomly assigned to one of six experimental groups and ventilated for 4 hours with: 1) Conventional HighVE Normocapnia (high VT, high minute ventilation, normocapnia), 2) Conventional Normocapnia (high VT, normocapnia), 3) Protective Normocapnia (VT 8ml/kg, high RR), 4) Conventional iCO2 Hypercapnia (high VT, low RR, added CO2), 5) Protective iCO2 Hypercapnia (VT 8ml/kg, high RR, added CO2), 6) Protective endogenous Hypercapnia (VT 8ml/kg, low RR). Blood gases, broncho-alveolar lavage fluid (BALF), and tissue specimens were collected and analyzed for histologic and biologic lung injury assessment. Results: Mild ALI was achieved in all groups characterized by a decreased mean PaO2/FiO2 ratio from 428 mmHg to 242 mmHg (p<0.05), and an increased mean elastance from 2.46 cmH2O/L to 4.32 cmH2O/L (p<0.0001). There were no differences in gas exchange between groups. Wet-to-dry ratios and formation of hyaline membranes were significantly lower in low VT groups compared to conventional tidal volumes. Hypercapnia ubiquitously reduced diffuse alveolar damage and IL-6 levels in the BALF, which was also true when CO2 was added to conventional VT. In low VT groups, hypercapnia did not induce any further protective effect except increasing pulmonary IL-10 in the BALF. No differences in lung injury were observed when hypercapnia was induced by adding CO2 or decreasing minute ventilation, although permissive hypercapnia decreased the pH significantly and decreased liver histologic injury. Conclusions: Our findings suggest that low tidal volume ventilation likely attenuates VALI by limiting mechanical damage to the lung, while hypercapnia attenuates VALI by limiting pro-inflammatory and biochemical mechanisms of injury. When combined, both lung-protective ventilation and hypercapnia have the potential to exert an additive effect for prevention of VALI.